2015
DOI: 10.1007/s11467-015-0478-9
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive gravitational effect of a quantum wave packet and experimental scheme with superfluid helium

Abstract: We consider the gravitational effect of quantum wave packets when quantum mechanics, gravity, and thermodynamics are simultaneously considered. Under the assumption of a thermodynamic origin of gravity, we propose a general equation to describe the gravitational effect of quantum wave packets. In the classical limit, this equation agrees with Newton's law of gravitation. For quantum wave packets, however, it predicts a repulsive gravitational effect. We propose an experimental scheme using superfluid helium to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In summary, we consider the thermodynamic origin of Newton’s gravitational force by considering simultaneously the spacetime entanglement entropy, the holographic principle, thermodynamics, and the Unruh effect for an accelerating particle. Different from previous works on the thermodynamic origin of gravitational force [ 2 , 51 , 52 , 53 ], in this work, we emphasize the quantum entanglement of spacetime. In the present paper, we do not use the assumption of the displacement entropy in [ 2 , 52 ], which implies a more solid basis for the thermodynamic origin of Newton’s gravitational force.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…In summary, we consider the thermodynamic origin of Newton’s gravitational force by considering simultaneously the spacetime entanglement entropy, the holographic principle, thermodynamics, and the Unruh effect for an accelerating particle. Different from previous works on the thermodynamic origin of gravitational force [ 2 , 51 , 52 , 53 ], in this work, we emphasize the quantum entanglement of spacetime. In the present paper, we do not use the assumption of the displacement entropy in [ 2 , 52 ], which implies a more solid basis for the thermodynamic origin of Newton’s gravitational force.…”
Section: Summary and Discussionmentioning
confidence: 96%
“…In summary, we consider the quantum thermodynamic origin of Newton's gravitational force by considering simultaneously the spacetime entanglement entropy, holographic principle, thermodynamics and the Unruh effect for an accelerating particle. Different from previous works on the thermodynamic origin of gravitational force [2,[32][33][34], in this work we emphasis on the quantum entanglement of spacetime. In the present paper, we do not use the assumption of the displacement entropy ∆S ∼ d in Refs.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the present paper, we do not use the assumption of the displacement entropy ∆S ∼ d in Refs. [2,33], which implies a more solid basis for the quantum thermodynamic origin of Newton's gravitational force.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…This entropy for displacement is used in Ref. [18] to understand the direction of gravitational force. At first sight, we may think that this is nonsense because there is no friction for this particle due to spacetime.…”
Section: Entanglement Entropy For Displacement Of a Particle And mentioning
confidence: 99%
“…In Ref. [18], based on the consideration of the loss of the information of the path, it is suggested that…”
Section: Entanglement Entropy For Displacement Of a Particle And mentioning
confidence: 99%